2021
DOI: 10.3390/vetsci8080151
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Corynebacterium pseudotuberculosis Isolated over a 15-Year Period in Switzerland

Abstract: Corynebacteriumpseudotuberculosis biovar Ovis is the etiological agent of the contagious and chronic disease caseous lymphadenitis (CLA) in sheep and goats. The economic impact of CLA in Switzerland remains largely unknown, and the transmission modalities, as well as the genetic diversity of circulating strains, are poorly understood. This work presents further characterization data for 215 C. pseudotuberculosis isolates from sheep, goats and a dromedary originating from Switzerland and the Principality of Lie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…These findings backed up previous studies by exotoxin, which found that the PLD produces ceramide phosphate, which is converted to ceramide by the PLC produced by R. equi, causing lipid bilayer rupture and RBC lysis in terms of biological activity (Williamson 2001 andSelim et al 2012). Molecular identification of C. pseudotuberculosis isolates which were recovered from vaccinated and non-vaccinated sheep were achieved successfully, this result was coincided with that reported by Mancini et al (2012) and Schlicher et al (2021).…”
Section: Discussionsupporting
confidence: 83%
“…These findings backed up previous studies by exotoxin, which found that the PLD produces ceramide phosphate, which is converted to ceramide by the PLC produced by R. equi, causing lipid bilayer rupture and RBC lysis in terms of biological activity (Williamson 2001 andSelim et al 2012). Molecular identification of C. pseudotuberculosis isolates which were recovered from vaccinated and non-vaccinated sheep were achieved successfully, this result was coincided with that reported by Mancini et al (2012) and Schlicher et al (2021).…”
Section: Discussionsupporting
confidence: 83%
“…C. pseudotuberculosis is divided into two biovars-biovar ovis and biovar equi-based on the differences in the results of the nitrate reduction test [3]. Although these biovars do not show strict host adaptation, the results of some studies and primarily sequencing data deposited at the National Center for Biotechnology Information (NCBI) show that the biovar ovis is mainly isolated from infections in small ruminants and the biovar equi from horses and large ruminants, e.g., dairy cattle [4,5].…”
Section: Introductionmentioning
confidence: 99%
“… C. pseudotuberculosis causes caseous lymphadenitis in small ruminants and edematous skin disease in buffaloes. Although this species is considered potentially toxigenic, only isolates from buffaloes in Egypt were reported to produce diphtheria toxin, and there is no evidence for toxigenicity of recent isolates from caseous lymphadenitis ( 6 9 ). Two novel species, C. belfantii and C. rouxii , were recently described ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%